Advances in the Processing and Application of Polymer and Its Composites - Wu, Wei; Mi, Hao-Yang; Huang, Chongxing; Zhao, Hui; Liu, Tao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book mainly focuses on the processing and applications of polymer and its composites. With the fast development of the petroleum industry, polymer materials have been widely utilized in our daily lives. The various processing methods of polymers determine the final properties and performance of products. In addition, the introduction of different fillers, including inorganic fillers, metal oxide, natural fibers, and so on, can increase the physical and chemical properties of polymer composites, which will further broaden their practical applications. Special attention will be paid to the type of processing methods and the functional fillers on the performance of polymer composites.